DETERMINANTS OF MATERIAL WELLBEING AMONG PARENTS OF CHILDREN WITH DISABILITIES - Salleh, Nurjannah; Md Jani, Syahrina Hayati; Mohd Noor, Abd Halim; Abdul Rasool, Mohamed Saladin (I-iECONS e-proceedings, 2023)
Previous study stated that both children and parents able commence deliberate behaviour and naturally adopt ways to affect the other's behaviour. They could assess their own behaviours and comprehend the information sent throughout the interaction. Parents of disabled children who suffer inadequate well-being unknowingly display negative parenting skills, making it difficult to help children with disabilities reach their full potential. When it comes to parenting, parents are always preoccupied. However, raising children with disabilities is a huge endeavour that has physical, psychological, and mental concerns for parents. To manage with their children's impairments, which are characterized by a wide spectrum of symptoms, parents frequently sacrifice their time, energy, and financial resources. In comparison to other disabilities, parents of children with autism spectrum disorder consistently reported greater levels of parental stress. The present models, however, are limited as indicators for assessing the well-being among parents of children with impairments. As a result, the goal of this research is to determine the level of material well-being and investigate the elements that influence it. In total, 230 Malaysian parents of children with disabilities took part in the study. To assess the research constructs and the structural model, smart partial least square (PLS) was used. The findings revealed that all the study hypotheses were supported, and the effect of the components inside the respondents' environment was confirmed. The results of this study showed that parents' financial attitudes, awareness of disabilities, and government support had a positive and significant impact on their children's material well-being. The study's anticipated outcome will help the government in developing plans to improve advanced and contemporary services for parents of children with disabilities.